Performance of Conventional Properties of Coal Bottom Ash, Waste Cooking Oil, and ZycoTherm-SP2 Binders - Yusuf Babangida Attahiru; Azman Mohamed; Norhidayah Abdul Hassan; Paramesvaran K.; Nurul Hidayah Mohd Kamaruddin (Mehran University Research Journal of Engineering and Technology)
This study presents the performance of Waste Cooking Oil (WCO), Coal Bottom Ash (CBA), and ZycoTherm-SP2 (ZT-SP2) as binder modifiers for warm mix Asphalt (WMA). The production of high-quality products depends on a reliable and well-regulated environment, with the control of mixing and compaction temperatures remaining a critical concern. This study aims to characterize the conventional properties of the bitumen binders by incorporating CBA, WCO, and ZT-SP2 in a controlled laboratory. The study's main contribution is the integration of a new warm mix chemical additive (ZT-SP2) into the binder mixtures which lowers the mixing and compaction temperatures by 30oC and 30 – 40oC, respectively. CBA, WCO, and ZT-SP2-modified binders were produced and characterized in the laboratory setup. The modifiers’ optimum contents were discovered to be 5%, 4%, and 0.1% respectively, and these optimum contents enhanced the bitumen's conventional properties. The modified binders’ viscosity (0.62 Pa.s) is appropriate for a range of situations that balance workability and permanent deformation resistance.